CONDITIONS AND PRINCIPLES OF VISUALIZATION OF TEXTUAL INFORMATION ON LEGAL KNOWLEDGE - Bekbergenova Guljamiyla Saparbaevna (Journals Park Publishing, 2025)
The effectiveness of any action, activity, and its acceptability for all is determined by its organization on the basis of established, generally accepted conditions and principles. Accordingly, the visualization of textual information on legal knowledge requires adherence to certain conditions and principles. The organization of the visualization of textual information on legal knowledge in accordance with the existing conditions and principles, on the one hand, helps to correctly organize pedagogical activity both cognitively and empirically, and on the other hand, provides students with educational information that is easy to understand and easily assimilated by them. The article discusses the main conditions and priority principles of visualization of textual information in teaching the subject "Fundamentals of State and Law" in general secondary schools.
Keywords: Legal knowledge, textual information, visualization, conditions, visualization conditions, principles, visualization principles.